Introducing mesoscopic charge transfer rates into molecular electronics - Santos, Adriano [UNESP]; Tefashe, Ushula M.; McCreery, Richard L.; Bueno, Paulo R. [UNESP] (Royal Society of Chemistry (RSC), 2020)
It has been demonstrated that mesoscopic rates operate in nanoscale electrochemical systems and, from a fundamental point of view, are able to establish a bridge between electrochemical and molecular electronic concepts. In the present work we offer additional experimental evidence in support of this statement.